UNRAVELING THE COMPLEX WEB: A MULTIDIMENSIONAL ANALYSIS OF THE ECONOMIC, POLITICAL, AND SOCIAL IMPLICATIONS OF BOYCOTTINGAMERICAN PRODUCTS AMIDST THE ISRAEL-PALESTINE CONFLICT - Indah Sulistiani; Loso Judijanto; Ahmad Rizani; Muhammad Faqih Annshori; Syarifuddin (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2023)
This study analyzes the economic, political, and social implications of boycotting American products within the context of the Israel-Palestine conflict. Employing a retrospective approach, the research delves into historical data to unravel the intricate web of consequences stemming from consumer activism. Quantitative and qualitative methods examine the economic impact on boycotted American companies, changes in diplomatic relationships, and shifts in public sentiment. The study contributes to existing literature by synthesizing findings and applying relevant economic, political, and sociological theories. The implications for policymakers, businesses, and advocacy groups are discussed, emphasizing the need for nuanced approaches to navigating the complexities of the conflict. In conclusion, the study reflects on the historical depth of the issue and the challenges inherent in comprehending the dynamic interplay between economic actions and geopolitical realities.